‘Asabiyyah & ‘Umran in Ibn Khaldun’s thought - Syed Jaafar, Syed Hamid Albar; Idid, Syed Arabi; Ra'ees, Wahabuddin Sahibuddin; Md. Noon, Hazizan (Serials Publications (P) Ltd., 2019)
Ibn Khaldun lived and experienced the decline of Muslims dominance in the early 13th and 14th centuries. He wrote on the history of the world in his “Kitab al Ibar” with an introduction chapter, the Muqaddimah based on his personal involvement in the various episodes, intrigues, observations and experience. He developed the theory of ‘umran and the role played by ‘asabiyyah in the rise and fall of ‘umran. Accordingly, this paper extensively discusses and analyses these two theories propounded by Ibn Khaldun with the aim to find out the connection between them in the rise and fall of a civilization and social order.